Amorphous silicon forming composition and method for producing amorphous silicon film using same
Patent Information
- Application Number
- JP2022521337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-21
- Filing Date
- 2020-11-18
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2040-11-18
AI Technical Summary
【0009】 本発明によると、基板との親和性が高いアモルファスシリコン形成組成物を提供することができる。
Smart Images

Figure 0007641278000001 
Figure 0007641278000002 
Figure 0007641278000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an amorphous silicon forming composition comprising a polysilane and a solvent, and a method for producing an amorphous silicon film using the same. [Background technology]
[0002] Electronic devices, especially semiconductor devices, are composed of thin films such as semiconductor films, insulating films, conductive films, etc. Silicon films are used as semiconductor films, as etching masks when processing insulating films, and as sacrificial films when manufacturing metal gates, etc.
[0003] Chemical vapor deposition (CVD), deposition, sputtering, and other methods are used to form amorphous silicon films and polycrystalline silicon films. At advanced nodes, using a gas-phase process such as CVD can cause excessive growth in narrow trenches, making it necessary to repeat etching and CVD. Therefore, films are formed by applying and baking a liquid composition containing a silicon-containing polymer. Hydrogenated polysilane is known as a silicon-containing polymer, but liquid compositions containing this have low affinity with substrates, and the cases in which films can be formed using this are very limited. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2013-43932 A [Patent Document 2] Japanese Patent Application Publication No. 6-192429 Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made based on the above-mentioned background art, and provides an amorphous silicon forming composition having high affinity with a substrate. In addition, an amorphous silicon film formed using this composition has resistance to hydrofluoric acid and can be removed with an alkaline aqueous solution. [Means for solving the problem]
[0006] The amorphous silicon forming composition according to the present invention comprises: Formula (I): [ka] (In the formula, p is a number between 5 and 1,000; Each X is independently selected from the group consisting of a hydrogen atom, a halogen atom, and a substituted or unsubstituted amino group; Each Y is independently selected from the group consisting of a single bond, a hydrogen atom, a halogen atom, -SiZ3, and a substituted or unsubstituted amino group, wherein Ys bonded to adjacent silicon atoms are not both single bonds; Each Z is independently selected from the group consisting of a single bond, a hydrogen atom, and a halogen atom; When Y or Z is a single bond, it joins the silicon atoms to which it is bonded together with other single bonds, provided that at least one of all X and Y is a substituted or unsubstituted amino group, and solvent The present invention relates to a method for producing a polymerizable composition comprising the steps of:
[0007] In addition, the method for producing an amorphous silicon film according to the present invention includes the steps of: Applying the amorphous silicon forming composition to a substrate to form a coating film; and Heating the coating in a non-oxidizing atmosphere The present invention relates to a method for producing a polymerizable composition comprising the steps of:
[0008] The method for producing an electronic device according to the present invention includes the method for producing an amorphous silicon film described above. The amorphous silicon film formed using this composition is resistant to hydrofluoric acid and can be removed with an alkaline aqueous solution. Effect of the Invention
[0009] According to the present invention, it is possible to provide an amorphous silicon forming composition having high affinity with a substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, embodiments of the present invention will be described in detail. In the following description, unless otherwise specified, the symbols, units, abbreviations, and terms have the following meanings.
[0011] In this specification, when a numerical range is indicated using the symbols ~, both end points are included and the units are the same. For example, 5 to 25 mol % means 5 mol % or more and 25 mol % or less.
[0012] In this specification, the term "hydrocarbon" refers to a group containing carbon and hydrogen and, where necessary, oxygen or nitrogen. The term "hydrocarbon group" refers to a monovalent or divalent or higher hydrocarbon group. In this specification, the term "aliphatic hydrocarbon" refers to a linear, branched or cyclic aliphatic hydrocarbon, and the term "aliphatic hydrocarbon group" refers to a monovalent or divalent or higher aliphatic hydrocarbon. The term "aromatic hydrocarbon" refers to a hydrocarbon containing an aromatic ring, which may have an aliphatic hydrocarbon group as a substituent or may be condensed with an alicyclic ring, if necessary. The term "aromatic hydrocarbon group" refers to a monovalent or divalent or higher aromatic hydrocarbon. These aliphatic hydrocarbon groups and aromatic hydrocarbon groups may contain fluorine, oxy, hydroxy, amino, carbonyl, or silyl, etc., if necessary. The term "aromatic ring" refers to a hydrocarbon having a conjugated unsaturated ring structure, and the term "alicyclic ring" refers to a hydrocarbon having a ring structure but not including a conjugated unsaturated ring structure.
[0013] In this specification, alkyl means a group in which one arbitrary hydrogen has been removed from a linear or branched saturated hydrocarbon, and includes linear alkyl and branched alkyl, and cycloalkyl means a group in which one hydrogen has been removed from a saturated hydrocarbon containing a cyclic structure, and optionally includes a linear or branched alkyl in the cyclic structure as a side chain.
[0014] In this specification, aryl refers to a group obtained by removing one arbitrary hydrogen from an aromatic hydrocarbon. Alkylene refers to a group obtained by removing two arbitrary hydrogens from a linear or branched saturated hydrocarbon. Arylene refers to a hydrocarbon group obtained by removing two arbitrary hydrogens from an aromatic hydrocarbon.
[0015] In this specification, "C x~y ", "C x ~C y " and "C x " refers to the number of carbons in a molecule or substituent. For example, C 1~6 Alkyl refers to an alkyl having 1 to 6 carbon atoms (methyl, ethyl, propyl, butyl, pentyl, hexyl, etc.). In addition, as used herein, fluoroalkyl refers to an alkyl group in which one or more hydrogen atoms have been replaced with fluorine, and fluoroaryl refers to an aryl group in which one or more hydrogen atoms have been replaced with fluorine.
[0016] In the present specification, when a polymer has multiple types of repeating units, these repeating units are copolymerized. The copolymerization may be any of alternating copolymerization, random copolymerization, block copolymerization, graft copolymerization, or a mixture thereof. In this specification, % means % by mass, and ratio means mass ratio.
[0017] In this specification, the unit of temperature is Celsius. For example, 20 degrees means 20 degrees Celsius.
[0018] <Amorphous Silicon Forming Composition> The amorphous silicon forming composition according to the present invention (hereinafter sometimes referred to as the composition) comprises a polysilane having a specific structure and a solvent.
[0019] (a) Polysilane The polysilane used in the present invention is represented by formula (I). [ka] During the ceremony, p is a number from 5 to 1,000, preferably from 10 to 500. Each X is independently selected from the group consisting of a hydrogen atom, a halogen atom, and a substituted or unsubstituted amino group, and preferably each X is independently selected from the group consisting of a hydrogen atom and a substituted or unsubstituted amino group. Each Y is independently selected from the group consisting of a single bond, a hydrogen atom, a halogen atom, -SiZ3, and a substituted or unsubstituted amino group, and preferably selected from the group consisting of a single bond, a hydrogen atom, -SiZ3, and a substituted or unsubstituted amino group. Each Z is independently selected from the group consisting of a single bond, a hydrogen atom, and a halogen atom, and is preferably a single bond or a hydrogen atom. Of the three Zs bonded to the same silicon atom, it is preferred that one of them is a single bond and the remaining two are hydrogen atoms or halogen atoms (preferably hydrogen atoms). When Y or Z is a single bond, it bonds to other single bonds contained in formula (I) and bonds the silicon atoms to which they are bonded. In this case, a ring is formed with the silicon atoms as members. Note that Ys bonded to adjacent silicon atoms do not both become single bonds and bond to each other. In other words, silicon atoms are not bonded to each other by double bonds. However, among all X and Y, one or more is a substituted or unsubstituted amino group. More preferably, one or more Y is an amino group.
[0020] The polysilane used in the present invention may or may not have a ring structure. In formula (I), when neither X nor Z is a single bond, the polysilane does not have a ring structure. Not having a ring structure is also a preferred embodiment of the present invention. When the polysilane has a ring structure, it may have two or more ring structures in one molecule. The ring structure is preferably a five-membered or six-membered ring, and more preferably a six-membered ring.
[0021] Preferably, the amino group is a group represented by formula (A) or (B). [ka] In the formula, R A1 and R A2 are each independently a hydrogen atom or C 1~12 Preferably, R A1 and R A2 are each independently a methyl group, an ethyl group, a butyl group, a propyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, or a nonyl group. [ka] During the ceremony, R B1 and R B2 are each independently a hydrogen atom or C 1~12 is an alkyl group of the formula R B3 are independently a hydrogen atom or C 1~4 Preferably, R B1 and R B2 are each independently a methyl group or an ethyl group, R B3 is a hydrogen atom or a methyl group.
[0022] More preferably, the amino group is a dialkylamino group, and even more preferably, the amino group is selected from the group consisting of di-n-butylamino group, diisobutylamino group, di-sec-butylamino group, diisopropylamino group, di-n-propylamino group, diethylamino group, and dimethylamino group.
[0023] Examples of polysilanes represented by formula (I) are as follows: [ka]
[0024] The polysilane represented by formula (I) has an amino group and does not have a Si-C bond. Without being bound by theory, it is believed that the presence of an amino group improves hydrophilic properties and exhibits affinity with hydroxyl groups on the substrate surface, thereby improving coatability. In addition, the absence of a Si-C bond is believed to result in high solubility in an alkaline solution after film formation, making etching with an alkaline solution possible.
[0025] The ratio of the number of N atoms to the number of Si atoms contained in the polysilane molecule (sometimes referred to as the "N / Si ratio" in the present invention) is preferably 0.1 to 40%, more preferably 0.3 to 35%. If the N / Si ratio is below 0.1%, the effect of the amino group is not observed, and if it exceeds 40%, precipitation may be observed due to the compatibility of the condensed polysilane with the amine. The N / Si ratio in the molecule can be calculated from the elemental ratio obtained by performing elemental analysis of a film formed using polysilane by Rutherford backscattering spectroscopy, for example. Specifically, it can be measured as follows. A polysilane solution containing the polysilane and a solvent used in the present invention is spin-coated on a 4-inch wafer at a rotation speed of 1,000 rpm using a spin coater (Mikasa Corporation's spin coater 1HDX2 (trade name)). The resulting coating film is baked at 240°C for 10 minutes in a nitrogen atmosphere. The baked film is subjected to elemental analysis by Rutherford backscattering spectroscopy using Pelletron 3SDH (trade name, National Electrostatics Corporation) to measure the atomic number ratio.
[0026] The mass average molecular weight of the polysilane used in the present invention is preferably 200 to 25,000, more preferably 300 to 15,000, from the viewpoints of solubility in a solvent, flatness of the film formed, and adhesion to a substrate. Here, the mass average molecular weight is a polystyrene-equivalent mass average molecular weight, and can be measured by gel permeation chromatography using polystyrene as a standard.
[0027] The method for producing the polysilane used in the present invention is not particularly limited, but may be, for example, (A) a step of irradiating a cyclic polysilane containing 5 or more silicon atoms with light; (B) preparing a mixture comprising an amine; (C) irradiating the mixture with light; It is produced by a method comprising: An example of the manufacturing method will be described below step by step.
[0028] (A) a step of irradiating a cyclic polysilane containing 5 or more silicon atoms with light The cyclic polysilane containing 5 or more silicon atoms (hereinafter, sometimes referred to as cyclic polysilane) can be selected arbitrarily as long as it does not impair the effects of the present invention. These may be either inorganic compounds or organic compounds, and may be linear, branched, or have a cyclic structure in part.
[0029] Preferably, the cyclic polysilane has the following formula (I'): [ka] (In the formula, each Y' is independently a hydrogen atom or a halogen atom, and q is a number of 5 or more.) As shown in the figure. Preferably, q is 5 to 8, and more preferably 5 or 6. Examples of preferred cyclic polysilanes include silylcyclopentasilane, silylcyclohexasilane, disilylcyclohexasilane, cyclopentasilane and cyclohexasilane, preferably cyclopentasilane or cyclohexasilane.
[0030] The wavelength in step (A) is preferably at least 172 to 405 nm, more preferably 282 to 405 nm. The irradiation intensity is preferably 10 to 250 mW / cm. 2 and more preferably 50 to 150 mW / cm 2 The irradiation time is preferably 30 to 300 seconds, and more preferably 50 to 200 seconds. Since cyclopentasilane or cyclohexasilane is a liquid at room temperature, the liquid cyclic polysilane can be irradiated with light while stirring. If the cyclosilane is a solid, it can be dissolved in a suitable solvent and irradiated with light while stirring. It is believed that the light irradiation in this step opens some or all of the cyclic polysilane rings.
[0031] (B) preparing a mixture comprising an amine The amine is selected from primary to tertiary amines, and is preferably an amine represented by formula (A') or (B'). [ka] In the formula, R A1’ and R A2’ are each independently a hydrogen atom or C 1~12 Preferably, R A1’ and R A2’ are each independently a methyl group, an ethyl group, a butyl group, a propyl group, a pentyl group, a hexyl group, a heptyl group, an octyl group, or a nonyl group. [ka] During the ceremony, R B1’ and R B2’ are each independently a hydrogen atom or C 1~12 is an alkyl group of the formula R B3’ are independently a hydrogen atom or C 1~4 Preferably, R B1’ and R B2’ are each independently a methyl group or an ethyl group, R B3’ is a hydrogen atom or methyl.
[0032] More preferably, the amine is a dialkylamine. Even more preferably, the amine is selected from the group consisting of di-n-butylamine, diisobutylamine, di-sec-butylamine, diisopropylamine, di-n-propylamine, diethylamine, dimethylamine.
[0033] When the irradiated cyclic polysilane is in a liquid state at room temperature, an amine is added and stirred to prepare a mixture. When the irradiated cyclic polysilane is in a solid state, it can be dissolved in a suitable solvent. It is also possible to prepare a mixture by dissolving an amine in a suitable solvent and then adding it to the irradiated cyclic polysilane and stirring it.
[0034] (C) A step of irradiating the mixture with light It is believed that the light irradiation in this process causes the amine to be added to the polysilane and causes condensation between the polysilanes. In this case, the exposure wavelength preferably includes at least a wavelength of 172 to 405 nm, and more preferably, 282 to 405 nm. The irradiation intensity is preferably 10 to 250 mW / cm. 2 and more preferably 50 to 150 mW / cm 2 The irradiation time is preferably 5 to 100 minutes, more preferably 5 to 60 minutes. The irradiation energy is preferably 3 to 1,500 J, more preferably 25 to 500 J. The above steps (A), (B) and (C) are preferably carried out in a non-oxidizing atmosphere.
[0035] (b) Solvent The composition according to the present invention comprises a solvent. The solvent is selected from those that uniformly dissolve or disperse each component contained in the composition. Specific examples of the solvent include ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, and ethylene glycol monobutyl ether, diethylene glycol dialkyl ethers such as diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, and diethylene glycol dibutyl ether, ethylene glycol alkyl ether acetates such as methyl cellosolve acetate and ethyl cellosolve acetate, propylene glycol monomethyl ether (PGME), propylene glycol monoethyl ... Examples of the propylene glycol monoalkyl ethers include propylene glycol monoethyl ether, propylene glycol alkyl ether acetates such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, and propylene glycol monopropyl ether acetate, aromatic hydrocarbons such as benzene, toluene, xylene, and mesitylene, ketones such as methyl ethyl ketone, acetone, methyl amyl ketone, methyl isobutyl ketone, and cyclohexanone, alcohols such as isopropanol and propanediol, and alicyclic hydrocarbons such as cyclooctane and decalin. Cyclooctane, toluene, decalin, and mesitylene are preferred. These solvents may be used alone or in combination of two or more.
[0036] In order to dissolve the polysilane homogeneously, the relative dielectric constant of the solvent is preferably 3.0 or less, more preferably 2.5 or less, as described in Solvent Handbook, 1st Edition, Kodansha Scientific.
[0037] The blending ratio of the solvent varies depending on the coating method and the required film thickness after coating, but the ratio of compounds other than the solvent (solid content ratio) is 1 to 96 mass %, preferably 96 mass % or more, and preferably 2 to 60 mass %.
[0038] The composition used in the present invention essentially contains the above-mentioned (a) and (b), but can be combined with additional compounds as necessary. The materials that can be combined are described below. The components other than (a) and (b) in the entire composition are preferably 10% or less, more preferably 5% or less, based on the total mass.
[0039] (c) Optional component Furthermore, the composition according to the present invention may contain optional components as necessary. Such optional components include, for example, a surfactant.
[0040] The use of a surfactant is preferred because it can improve the coating properties. Examples of surfactants that can be used in the siloxane composition of the present invention include nonionic surfactants, anionic surfactants, and amphoteric surfactants.
[0041] Examples of the nonionic surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene oleyl ether, and polyoxyethylene cetyl ether; polyoxyethylene fatty acid diesters, polyoxyethylene fatty acid monoesters, polyoxyethylene polyoxypropylene block polymers; acetylene alcohol, acetylene glycol, acetylene alcohol derivatives such as polyethoxylate of acetylene alcohol, acetylene glycol derivatives such as polyethoxylate of acetylene glycol; fluorine-containing surfactants such as Fluorad (trade name, manufactured by 3M Limited), Megafac (trade name, manufactured by DIC Corporation), and Sulfuron (trade name, manufactured by Asahi Glass Co., Ltd.); and organic siloxane surfactants such as KP341 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.). Examples of the acetylene glycol include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,6-dimethyl-4-octyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 3,5-dimethyl-1-hexyne-3-ol, 2,5-dimethyl-3-hexyne-2,5-diol, and 2,5-dimethyl-2,5-hexanediol.
[0042] Examples of the anionic surfactant include ammonium salts or organic amine salts of alkyldiphenyl ether disulfonic acids, ammonium salts or organic amine salts of alkyldiphenyl ether sulfonic acids, ammonium salts or organic amine salts of alkylbenzene sulfonic acids, ammonium salts or organic amine salts of polyoxyethylene alkyl ether sulfates, and ammonium salts or organic amine salts of alkyl sulfates.
[0043] Further, examples of amphoteric surfactants include 2-alkyl-N-carboxymethyl-N-hydroxyethylimidazolium betaine, lauric acid amidopropyl hydroxysulfone betaine, and the like.
[0044] These surfactants can be used alone or in combination of two or more kinds, and the blending ratio thereof is usually 50 to 10,000 ppm, preferably 100 to 5,000 ppm, based on the total mass of the composition.
[0045] <Method for manufacturing amorphous silicon film> A method for producing an amorphous silicon film according to the present invention comprises applying the above-mentioned amorphous silicon forming composition to a substrate to form a coating film, and heating this coating film in a non-oxidizing atmosphere. In the present invention, the term "on a substrate" includes cases where the composition is applied directly to the substrate, and cases where the composition is applied to the substrate via one or more intermediate layers.
[0046] The method of applying the composition to the surface of the substrate can be selected from conventionally known methods such as spin coating, dipping, spraying, transfer, roll coating, bar coating, brush coating, doctor coating, flow coating, and slit coating. As the substrate to which the composition is applied, a suitable substrate such as a silicon substrate, a glass substrate, or a resin film can be used. Various semiconductor elements may be formed on these substrates as necessary. When the substrate is a film, gravure coating can also be used. If desired, a drying step can be separately provided after the coating. If necessary, the coating step can be repeated once or twice or more to obtain a coating film having a desired thickness.
[0047] After forming a coating film of the composition according to the present invention, the coating film may be prebaked (heat-treated) in order to dry the coating film and reduce the amount of remaining solvent. The prebaking step can be carried out in a non-oxidizing atmosphere, preferably at a temperature of 80 to 200°C, for 10 to 300 seconds when using a hot plate, or for 1 to 30 minutes when using a clean oven. In the present invention, the non-oxidizing atmosphere refers to an atmosphere having an oxygen concentration of 1 ppm or less and a dew point of -76°C or less. The preferred atmosphere is N2, Ar, He, Ne, H2, or a mixed gas atmosphere of two or more of these.
[0048] Then, the coating is heated to harden the coating film to form an amorphous silicon film. The heating temperature in this heating step is not particularly limited as long as it is a temperature at which a coating film having appropriate crystallinity can be obtained, and can be determined arbitrarily. However, the chemical resistance of the cured film may become insufficient, or the dielectric constant of the cured film may become high. From this viewpoint, the heating temperature is generally selected to be relatively high. In order to promote the curing reaction and obtain a sufficient cured film, the curing temperature is preferably 200°C or higher, more preferably 300°C or higher. In general, since the crystallization of amorphous silicon progresses, the curing temperature is preferably 1,000°C or lower. In addition, the heating time is not particularly limited, and is generally 10 minutes to 24 hours, preferably 0.001 seconds to 24 hours. The heating may be performed by flash annealing. The heating time is the time after the temperature of the coating film reaches the desired heating temperature. Usually, it takes several seconds to several hours for the pattern film to reach the desired temperature from the temperature before heating. In addition, the atmosphere during curing is preferably a non-oxidizing atmosphere.
[0049] After forming a coating film using the composition according to the present invention, the coating film can be irradiated with an electron beam or light before the curing step. By irradiating the coating film with an electron beam or light, it is possible to suppress a decrease in film thickness during the curing step. The light irradiation is preferably performed with light having a wavelength of 172 to 436 nm, more preferably 248 to 405 nm. The irradiation intensity is preferably 10 to 800 mW / cm. 2 and more preferably 40 to 600 mW / cm 2 The irradiation time is preferably 30 to 3,500 seconds, and more preferably 50 to 3,000 seconds.
[0050] The thickness of the formed cured film is not particularly limited, but is preferably from 5 nm to 1 μm, and more preferably from 10 to 500 nm.
[0051] The crystallinity of the formed cured film can be evaluated by X-ray diffraction (XRD), where if no diffraction peaks of crystalline silicon are observed after curing, the cured film is confirmed to be made of amorphous silicon.
[0052] The use of this amorphous silicon film is not limited. This amorphous silicon film is easily dissolved in an alkaline aqueous solution, and therefore can also be used as a sacrificial film. An appropriate alkaline aqueous solution is selected depending on the cured film formed. Examples of the alkaline aqueous solution include potassium hydroxide, sodium hydroxide, ammonia water, and tetramethylammonium hydroxide (TMAH) aqueous solution. For example, the etching rate in a 10 mass % potassium hydroxide aqueous solution at room temperature (20 to 30°C) is preferably 0.1 to 1,000 Å / min, and more preferably 10 to 1,000 Å / min. On the other hand, this amorphous silicon film has resistance to hydrofluoric acid aqueous solution and the like. Specifically, the etching rate in a 0.5 mass % hydrofluoric acid aqueous solution at room temperature is preferably 0 to 200 Å / min, and more preferably 0 to 50 Å / min. The resistance to alkaline aqueous solution can also be adjusted by adjusting the manufacturing conditions of the amorphous silicon film. By increasing the heating temperature or the heating time when forming the amorphous silicon film, the resistance to an alkaline aqueous solution can be increased.
[0053] The method for producing an electronic device according to the present invention includes the above-mentioned production method. The method for producing an electronic device may further include a step of removing the amorphous silicon film with an alkaline aqueous solution or the like as described above.
[0054] The present invention will now be described with reference to examples, which are for illustrative purposes only and are not intended to limit the scope of the present invention. In the following description, "parts" are by mass unless otherwise specified.
[0055] All of the polysilane synthesis and composition preparation steps in the following Examples and Comparative Examples are carried out in a glove box under a nitrogen atmosphere with an oxygen concentration of 0.1 ppm or less and a dew point temperature of -76.0°C or less.
[0056] Example 1 A stirrer tip was placed in a 6 mL screw tube, 250.18 mg of cyclohexasilane was added, and while stirring using a stirrer, 4.9 J / cm of ultraviolet light with a wavelength of 365 nm from an LED lamp was applied. 2 After UV irradiation, 35.08 mg of diisopropylamine is added and the mixture is stirred using a stirrer. While stirring, UV rays with a wavelength of 365 nm from an LED lamp as a light source are applied at 4.9 J / cm. 2 After the ultraviolet irradiation, cyclooctane is added so that the polysilane concentration becomes 19 mass %, and the mixture is stirred for 3 minutes and filtered using a 0.2 μm PTFE filter (Advantec, DISMIC-13JP) to prepare amorphous silicon forming composition A. The weight average molecular weight of the synthesized polysilane is 880, and the N / Si ratio measured by Rutherford backscattering spectroscopy is 4.2%.
[0057] Amorphous silicon forming composition A is applied to a Si substrate in a nitrogen atmosphere using a spin coater (Mikasa Co., Ltd. spin coater 1HDX2 (product name)) to form a coating film. The resulting coating film is heated on a hot plate at 400°C for 15 minutes to obtain an amorphous silicon film. The amorphous silicon film obtained is measured by secondary ion mass spectrometry (SIMS) to find the composition as follows: Si: 94.95 mass%, O: 0.52 mass%, N: 1.98 mass%, C: 2.55 mass%, and XRD shows no diffraction peak of crystalline Si, confirming that the film is amorphous silicon. The resulting amorphous silicon film had a thickness of 33.3 nm and a refractive index (633 nm) of 3.22. The amorphous silicon film thus obtained was etched with a 10% by mass potassium hydroxide aqueous solution at an etching rate of 55 nm / min. On the other hand, when etched with a 0.5% by mass hydrofluoric acid aqueous solution, the etching rate was 0.3 nm / min, and the film had HF resistance.
[0058] Example 2 A stirrer tip is placed in a 6 mL screw tube, 240.56 mg of cyclohexasilane is added, and the mixture is stirred using a stirrer. While stirring, 4.9 J / cm2 of ultraviolet light with a wavelength of 365 nm from an LED lamp is applied to the mixture. 2 After UV irradiation, 19.95 mg of di-n-butylamine was added, and the mixture was exposed to 14.7 J / cm2 UV light with a wavelength of 365 nm from an LED lamp as a light source. 2 The mixture is irradiated and then heated to 40° C. and stirred for 30 minutes to form polysilane. Cyclooctane is added so that the polysilane concentration becomes 19% by mass, and the mixture is stirred for 3 minutes and filtered using a 0.2 μm PTFE filter to prepare amorphous silicon forming composition B. The weight average molecular weight of the synthesized polysilane is 1,250, and the N / Si ratio measured by Rutherford backscattering spectroscopy is 1.9%.
[0059] The amorphous silicon forming composition B is applied to a Si substrate in a nitrogen atmosphere using a spin coater to form a coating film. The resulting coating film is heated on a hot plate at 400°C for 15 minutes to obtain an amorphous silicon film. The resulting film is measured by secondary ion mass spectrometry to find that it contains 94.70% by mass of Si, 0.46% by mass of O, 1.53% by mass of N, and 3.31% by mass of C. XRD does not reveal any diffraction peaks of crystalline Si, confirming that the film is amorphous silicon. The resulting amorphous silicon film had a thickness of 92.0 nm and a refractive index (633 nm) of 3.68. The amorphous silicon film thus obtained was etched in a 10% by mass aqueous solution of potassium hydroxide at an etching rate of 60 nm / min, whereas the film was etched in a 0.5% by mass aqueous solution of hydrofluoric acid at an etching rate of 0.2 nm / min, demonstrating HF resistance.
[0060] Example 3 A stirrer tip is placed in a 6 mL screw tube, 249.96 mg of cyclohexasilane is added, and the mixture is stirred using a stirrer. While stirring, 4.9 J / cm of ultraviolet light with a wavelength of 365 nm from an LED lamp is applied to the mixture. 2 After UV irradiation, 35.98 mg of 1,1,2-trimethylhydrazine was added, and while stirring, UV rays with a wavelength of 365 nm from an LED lamp as a light source were applied at 14.7 J / cm. 2 The mixture is irradiated to form polysilane, and cyclooctane is added thereto so that the concentration of polysilane becomes 19% by mass, followed by stirring for 3 minutes and filtering using a 0.2 μm PTFE filter to prepare amorphous silicon forming composition C. The weight average molecular weight of the synthesized polysilane is 1,380, and the N / Si ratio measured by Rutherford backscattering spectroscopy is 11.7%.
[0061] The amorphous silicon forming composition C is applied to a Si substrate in a nitrogen atmosphere using a spin coater to form a coating film. The resulting coating film is heated on a hot plate at 400°C for 15 minutes to obtain an amorphous silicon film. Since no diffraction peak of crystalline Si was observed from XRD, it is confirmed that the film is amorphous silicon. The resulting amorphous silicon film had a thickness of 63.7 nm and a refractive index (633 nm) of 3.67. The amorphous silicon film thus obtained was etched in a 10% by mass aqueous solution of potassium hydroxide at an etching rate of 32 nm / min, whereas the film was etched in a 0.5% by mass aqueous solution of hydrofluoric acid at an etching rate of 0.3 nm / min, demonstrating HF resistance.
[0062] Example 4 A stirrer tip is placed in a 6 mL screw tube, 250.31 mg of cyclohexasilane is added, and stirring is performed using a stirrer. While stirring, ultraviolet light with a wavelength of 365 nm from an LED lamp as a light source is applied at 3.3 J / cm. 2 After UV irradiation, 7.16 mg of diisopropylamine was added, and while stirring, UV light with a wavelength of 365 nm from an LED lamp was applied at 14.8 J / cm. 2 The mixture is irradiated to form polysilane, and cyclooctane is added thereto so that the concentration of polysilane becomes 19% by mass, followed by stirring for 3 minutes and filtering using a 0.2 μm PTFE filter to prepare amorphous silicon forming composition D. The weight average molecular weight of the synthesized polysilane is 1,630, and the N / Si ratio measured by Rutherford backscattering spectroscopy is 0.85%.
[0063] Amorphous silicon forming composition D is applied to a Si substrate in a nitrogen atmosphere using a spin coater to form a coating film. The resulting coating film is heated on a hot plate at 400°C for 15 minutes to obtain an amorphous silicon film. Since no diffraction peak of crystalline Si was observed from XRD, it is confirmed that the film is amorphous silicon. The resulting amorphous silicon film had a thickness of 120.2 nm and a refractive index (633 nm) of 3.80. The amorphous silicon film thus obtained was etched in a 10% by mass aqueous solution of potassium hydroxide at an etching rate of 62 nm / min, whereas the film was etched in a 0.5% by mass aqueous solution of hydrofluoric acid at an etching rate of 0.2 nm / min, demonstrating HF resistance.
[0064] Example 5 A stirrer tip is placed in a 6 mL screw tube, 250.13 mg of cyclohexasilane is added, and stirring is performed using a stirrer. While stirring, ultraviolet light with a wavelength of 365 nm from an LED lamp as a light source is applied at 3.3 J / cm. 2After UV irradiation, 326.5 mg of diisopropylamine was added, and while stirring, UV rays with a wavelength of 365 nm from an LED lamp as a light source were irradiated at 14.8 J / cm. 2 The mixture is irradiated to form polysilane, and cyclooctane is added thereto so that the concentration of polysilane becomes 19% by mass, followed by stirring for 3 minutes and filtering using a 0.2 μm PTFE filter to prepare amorphous silicon forming composition E. The weight average molecular weight of the synthesized polysilane is 1,040, and the N / Si ratio measured by Rutherford backscattering spectroscopy is 39%.
[0065] The amorphous silicon forming composition E is applied to a Si substrate in a nitrogen atmosphere using a spin coater to form a coating film. The resulting coating film is heated on a hot plate at 400°C for 15 minutes to obtain an amorphous silicon film. Since no diffraction peak of crystalline Si was observed from XRD, it is confirmed that the film is amorphous silicon. The resulting amorphous silicon film had a thickness of 28.7 nm and a refractive index (633 nm) of 3.82. The amorphous silicon film thus obtained was etched in a 10% by mass aqueous solution of potassium hydroxide at an etching rate of 28 nm / min, whereas the film was etched in a 0.5% by mass aqueous solution of hydrofluoric acid at an etching rate of 0.2 nm / min, demonstrating HF resistance.
[0066] Comparative Example 1 A stirrer tip is placed in a 6 mL screw tube, 272 mg of cyclohexasilane is added, and the tube is stirred using a stirrer. 8.6 J / cm of ultraviolet light with a wavelength of 365 nm from a mercury xenon light source is applied to the tube. 2 After irradiation, the ultraviolet light with a wavelength of 365 nm from a mercury xenon light source is applied at 98.4 J / cm 2 Irradiate and stir for 20 minutes. Then, add cyclooctane so that the solid content concentration is 19 mass%, and stir for 3 minutes. Then, filter using a 5.0 μm PTFE filter and a 0.2 μm PTFE filter to obtain a comparative composition A.
[0067] Comparative composition A was applied to a Si substrate in a nitrogen atmosphere using a spin coater in an attempt to form a coating film, but comparative composition A did not adhere to the substrate and no film was formed.
Claims
1. Formula (I): 【Chemistry 1】 (In the formula, p is a number from 10 to 1,000; Each X is independently selected from the group consisting of a hydrogen atom, a halogen atom, and a substituted or unsubstituted amino group; Each Y is independently a single bond, a hydrogen atom, a halogen atom, or -SiZ 3 and a substituted or unsubstituted amino group, wherein Y's bonded to adjacent silicon atoms are not both single bonds; Each Z is independently selected from the group consisting of a single bond, a hydrogen atom, and a halogen atom; When Y or Z is a single bond, it bonds the silicon atoms to which it is bonded together with other single bonds, provided that at least one of all X and Y is a substituted or unsubstituted amino group, and solvent 1. An amorphous silicon forming composition comprising:
2. The composition according to claim 1 , wherein the amino group is a group represented by formula (A) or (B). 【Chemistry 2】 (In the formula, R A1 and R A2 Each independently represents a hydrogen atom or C 1~12 is an alkyl group of the formula 【Chemistry 3】 (In the formula, R B1 and R B2 Each independently represents a hydrogen atom or C 1~12 is an alkyl group of the formula R B3 are independently a hydrogen atom or C 1~4 is an alkyl group of the formula
3. The composition according to claim 1 or 2, wherein the amino group is a dialkylamino group.
4. The composition according to any one of claims 1 to 3, wherein the amino group is selected from the group consisting of a di-n-butylamino group, a diisobutylamino group, a di-sec-butylamino group, a diisopropylamino group, a di-n-propylamino group, a diethylamino group, and a dimethylamino group.
5. The composition of any one of claims 1 to 4, wherein one or more Y's are amino groups.
6. 6. The composition according to claim 1, wherein the polysilane has a mass average molecular weight of 200 to 25,000 in terms of polystyrene as measured by gel permeation chromatography.
7. 7. The composition according to claim 1, wherein the ratio of the number of N atoms to the number of Si atoms contained in the polysilane molecule is 0.1 to 40%.
8. The composition according to any one of claims 1 to 7, wherein the solvent has a relative dielectric constant of 3.0 or less.
9. Applying the composition according to any one of claims 1 to 8 to a substrate to form a coating film; and Heating the coating in a non-oxidizing atmosphere A method for producing an amorphous silicon film comprising the steps of:
10. The method according to claim 9, wherein the heating is carried out at 200 to 1,000°C.
11. 11. An electronic device manufactured by comprising the method of claim 9 or 10.
Citation Information
Patent Citations
Polyester having reactive groups at both molecular ends and its production
JP1994192429A
Silane polymer and method for forming silicon film
JP2005022964A
Process for producing polysilane
JP2013043932A
Monoaminosilane compound
JP2017523134A
Higher-order silane composition and method for producing substrate with film
WO2010079842A1